Analisis Pengelolaan Arsip Sebagai Upaya Meningkatkan Pelayanan Administrasi di Kantor Desa Wirokerten - Muhammad Rosyid Nugroho (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Archive management is a crucial aspect in supporting the quality of administrative services at the village level, including at the Wirokerten Village Office. This study uses a qualitative method with a descriptive approach that emphasizes field observation, documentation studies, and analysis of physical and digital archive data. The results of the observation show that the implementation of systematic and integrated management of physical and digital archives can accelerate the process of administrative document services, improve the accuracy of data verification, and support the accountability and transparency of public services. The findings also indicate that the main obstacles still lie in old archives that have not been digitized and limited archival infrastructure, thus requiring further optimization. This study confirms that effective archive management is a strategic instrument for improving the responsiveness, efficiency, and professionalism of village administrative services. The practical implications include the development of a digital archive retrieval system and increased human resource capacity in archive management.